Augmented reality in smart retailing: A (n) (A) Symmetric Approach to continuous intention to use retail brands’ mobile AR apps - Nikhashemi, S. R.; Knight, H. H.; Khaldoon, N.; Cheng, Boon Liat * (Elsevier, 2021)
Smart retailing has recently emerged as a new form of retail brand management enabled by novel technologies such as mobile augmented reality applications, to create better experience and value for customers. Augmented reality has also received significant attention as a growing field in marketing theory and practice. However, there is a limited understanding on how and why customer interactions with an augmented reality app can result in positive customer benefit perception, engagement and behavioural consequences. This study examines the chain of effects from AR attributes on the building blocks of continuous intention to use a shopping AR app and to pay a price premium, by incorporating the roles of a customer’s benefits perception, psychological inspiration and engagement via a(n) (A)Symmetric Approach. The results support all direct hypothesised relationships among the variables, except the relationship between interactivity and utilitarian benefits, which was found to be insignificant. The study further demonstrates the moderating role of AR customisation in the proposed model, and reveals that the impact of utilitarian and hedonic benefits on shopping AR application engagement is nonlinear. Non-linearity also transpires in the impact of psychological inspiration on willingness to pay price premium. Interestingly, the findings indicate that augmented reality customisation to some extent enhances the relationships in the hypothesised model.